1986
DOI: 10.1007/bf00869260
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of erythrocyte (Na+-K+)ATPase activity in Type 1 (insulin-dependent) diabetic subjects and its activation by homologous plasma

Abstract: The (Na+-K+)ATPase and (Mg2+)ATPase activities of erythrocyte membranes of Type 1 (insulin-dependent) diabetic patients were found to be significantly reduced compared to matched controls (p less than 0.005). On the contrary, erythrocyte Na+ and K+ contents were similar in diabetic patients and in normal subjects. When erythrocyte membranes from diabetic patients were incubated with their own plasma, a significant increase was observed in sodium-potassium ATPase activity (p less than 0.005), whereas (Mg2+)ATPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 29 publications
6
53
0
Order By: Relevance
“…In this study, we confirmed our previous finding [3,4,5,6] that diabetic neuropathy is associated with lower erythrocyte Na/K ATPase in Type I diabetic patients. The same finding was also observed in Type II diabetic patients.…”
Section: ±1supporting
confidence: 92%
“…In this study, we confirmed our previous finding [3,4,5,6] that diabetic neuropathy is associated with lower erythrocyte Na/K ATPase in Type I diabetic patients. The same finding was also observed in Type II diabetic patients.…”
Section: ±1supporting
confidence: 92%
“…We have previously demonstrated that the cardiospermum halicacabum leaf extract (CHE) is having antihyperglycaemic, antioxidant, antiglycation and antihyperlipidemic activity on STZ-induced diabetic rats (Veeramani et (Finotti and Palatini, 1986). Hence, the present study we observed that the decrease activity of Na + /K + -ATPase may be considered as an index of cardiovascular complications induced by diabetes.…”
Section: Discussionsupporting
confidence: 49%
“…In patients with IDDM, we and others [12][13][14][15][16] have reported depressed Na/K ATPase activity in erythrocyte membranes; this decrease probably reflects a decrease in nerve tissue. In this regard we showed a parallel decrease of Na/K ATPase activity in both erythrocytes and sciatic nerve of diabetic rats [17].…”
Section: Discussionmentioning
confidence: 60%
“…This transport not only maintains sodium and potassium concentration gradients between the intracellular and extracellular milieus, but is also critical to a number of important processes including membrane potential generation and nerve conduction [11]. A decrease in Na/K ATPase activity has been reported in the erythrocytes of IDDM patients and diabetic rats [12][13][14][15][16][17]. Moreover, the impairment of this enzyme activity is proportional in sciatic nerve and erythrocytes of diabetic rats [17].…”
mentioning
confidence: 99%